The Politics of Race and Ethnicity in the United States Americanization, De-Americanization, and Racialized Ethnic Groups - Pinder, Sherrow O. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2010)
The purpose of this book is to examine and analyze Americanization, De-Americanization, and racialized ethnic groups in America and consider the questions: who is an American? And what constitutes American identity and culture?